Integrated Project Delivery (Ipd): A Collaborative Approach to Improve the Construction Industry - Abdul Rahim, Syukran; Mohd Nawi, Mohd Nasrun; Abdul Nifa, Faizatul Akmar (Asian Research Publishing Network (ARPN), 2016)
The Malaysian construction industry is depreciating in comparison to other sectors where most of the construction supplies and materials have increased to unreasonable prices. This issue is bringing down the value of the projects which resulted in the construction players are not deriving any benefit from the projects. This will further demoralise the construction players, in addition to the inherent problem of fragmentation issues in the construction which is already killing the industry. The current building method is no longer relevant to to the industry anymore due to the lack of controlling specifically on the subject of cost leaking.he other issues that are leading to cost leaking such as rework, delay and wastage, are also causing threats to the survival of organizations within the construction industry. Consequently, this paper through the literature review highlights fragmentation as the primary issue in the construction industry and suggests the Integrated Project Delivery (IPD) as the result of all those events that had been placed